Mean Systemic Filling Pressure Was Associated with 28-Day Mortality in Patients with Constrictive Pericarditis After Pericardial Stripping: A Retrospective Cohort Study - Chen R; Du W (International Journal of General Medicine)
Rongping Chen,1 Wei Du2 1Department of Critical Care Medicine, The First Affiliated Hospital, Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2Department of Critical Care Medicine, Peking Union Medical College Hospital, Peking Union Medical College & Chinese Academy of Medical Sciences, Beijing, People’s Republic of ChinaCorrespondence: Wei Du, Peking Union Medical College Hospital, Peking Union Medical College & Chinese Academy of Medical Sciences, Beijing, 13691018276, People’s Republic of China, Email duwpumch@126.comIntroduction: This study aimed to explore changes in the venous return system in patients with Constrictive pericarditis (CP) after pericardial stripping and examine their value in predicting mortality.Methods: An 8-year single-center retrospective cohort study including patients with CP after pericardial stripping surgery. Hemodynamic parameters were analyzed in 90 patients at 11 time points including before and after surgery and every 4 to 9 hours in the first 48 hours in the ICU (pre-operation, post-operation, 0h, t1, t2, t3, 24h, t4, t5, t6, 48h).Results: Mean systemic filling pressure (Pmsf) were significantly higher in patients who died (non-survival group) than survivors (P = 0.016, respectively). Pmsf at 24h, APACHE II score, and SOFA score were evaluated as predictors of 28-day mortality. APACHE II combined with Pmsf at 24h had the highest prediction (AUC 0.807; 95% confidence interval, 0.671– 0.941; P = 0.003).Discussion: In conclusion, Pmsf at 24h can be used as a valid indicator for prognostic assessment in patients with constrictive pericarditis admitted after pericardial stripping. Pmsf at 24h improves the performance of APACHE II scores in predicting 28-day mortality. Closely monitoring of Pmsf in patients after pericardial debridement may provide guidance for clinical management.Keywords: venous return, hemodynamic monitoring, intensive care unit, pericardial stripping surgery, mortality